2010
DOI: 10.1055/s-0029-1246159
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Endoscopic Thoracic Discectomy; Transforaminal Approach

Abstract: As it has been proven to lessen the morbidity rate, this percutaneous endoscopic thoracic discectomy (PETD) technique for symptomatic soft TDH is a safe and effective method that provides a direct route to the lesion under local anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 3 publications
(4 reference statements)
0
65
0
1
Order By: Relevance
“…PETD is one type of minimally invasive spinal surgery, whose procedures are derived from the percutaneous endoscopic lumbar discectomy (PELD) that would be a promising alternative to the MED technique as well as microscope-assisted technique [11][12][13]. Because of the differences between lumbar anatomy and thoracic anatomy, the canal and nerve root, any detailed step of PETD must be more precise from that of PELD, which has a greater degree of safety that can compensate the position of movable cannulas in the foramen.…”
Section: Discussionmentioning
confidence: 99%
“…PETD is one type of minimally invasive spinal surgery, whose procedures are derived from the percutaneous endoscopic lumbar discectomy (PELD) that would be a promising alternative to the MED technique as well as microscope-assisted technique [11][12][13]. Because of the differences between lumbar anatomy and thoracic anatomy, the canal and nerve root, any detailed step of PETD must be more precise from that of PELD, which has a greater degree of safety that can compensate the position of movable cannulas in the foramen.…”
Section: Discussionmentioning
confidence: 99%
“…This encouraging result suggests that our surgical technique is effective in improving the symptoms of thoracic herniations at different disc levels. When using a similar technique to treat soft thoracic disc herniations, Choi et al also achieved satisfying results [28], which indicates the technique is reproducible.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of minimally invasive techniques have compelled many physicians to explore the feasibility of using minimally invasive techniques in treating thoracic disc herniation, and a number of authors have reported encouraging primary results [14, 2528]. Based on our extensive experience with treating lumbar and cervical disc herniation using minimally invasive techniques, we have developed an endoscopic transforaminal foraminotomy and discectomy technique for treating thoracic disc herniation.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 With improved surgical access and better surgical instruments, a broader spectrum of thoracic spinal disease becomes accessible. 27,28 …”
Section: Thoracic Spinementioning
confidence: 99%